BENTUK KEKERASAN DALAM FILM â€œHAN GONG JUâ€ (ANALISIS ISI PADA FILM â€œHAN GONG JUâ€) - Rusmana, Dewi Sri Andika (Universitas 17 Agustus 1945 Surabaya, 2019)
Film does not only provide entertainment for the audiences but also raises a realitythat exists in society. Not all films can be enjoyed by all audiences. This is becausethe scenes in the film contain elements of violence, mysticism, sex and other elements.The film of Han Gong Ju is a film adapted from an incident of rape in the Miryangarea, South Korea. This film contains elements of violence. Violence is divided intothree, namely physical, symbolic and sexual violence. The method used in this studyis descriptive content analysis. The results in this study are the existence of elementsof violence both physical, symbolic and sexual violence. The violence is notindividual, but collectively.Keyword: film, han gong ju, violences, content analysis